Mensuração econômica da cadeia interna de valor do segmento madereiro de pinus: o caso da empresa Madepar Ltda - Bleil, Claudecir (Universidade do Vale do Rio do Sinos, 2007)
This survey was made in order to analyze the value chain as a necessary management tool. And this tool it is really needed to formulate strategies for the organizations to develop competitive advantages in the market they act, emphasizing the necessity of information. In this context, the project had the objective of measuring the inside value chain of the pinus processing as a way to present the result and the contribution of each stage of the process into the economical result. About the method, it had been used an explorer research, based in a case studied in a wood industry, that acts from the seed plantation to the delivery of the favoured pinus wood to costumers. Based in some techniques and methods of strategic costs management, for example the Direct Cost method, the Transference Price (Market Price) and the Opportunity Cost. It had been developed samples of management reports in the value chain point of view. As a result, it has been noticed that the present project tried to contribute to taste and c
Keywords: cadeia de valor; cadeia interna; custos; estratégias competitivas; gestão estratégica; competitive strategies; inside value chain; management; value chain; strategic costs; Ciências Sociais Aplicadas